Managing sport, fitness, and recreation programs : concepts and practices - Stier, William F. (Allyn and Bacon, 1999)
This book is provides the readers a realistic glimpse into the challenges and opportunities that exist now as well as in the future within the exciting world of sport and sport management, with a comprehensive introduction to the body of knowledge that serves as the foundation for the study of management within sport and sport-related organization.